(3QSGdI eNJUQI aj JaSjQ bhdg JYGdi (B: ( (3djZaQ dc Gddg heG JbOe ef PfHc heG JCNQ (B)s
(3ChdgG (B:s
(3djZaQdc Gddg eG JbOe ef PfHc heG JCNQ gPg GdCjI ajgG CbhGd eaSQjf HYVgG ebHhd hHYVgG eQOhO hHYVgG VYja HGdOdjd GdbGWY s
(3BNQgG (B:s
(3aEPG de jaYdhG hJGH Gddg Ydjce hYfO fSN JMQje GdLeGY (B" (3aJGH Ydjce hYai Yfce aGdBf HGTQhgf GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhd eNJdaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs